PELATIHAN KECAKAPAN VOKASIONAL UNTUK MENINGKATKAN KEMANDIRIAN SOSIAL EKONOMI INDIVIDU EKS PSIKOTIK DI UPT REHABILITASI SOSIAL EKS PSIKOTIK PROVINSI JAWA TIMUR - Muh. Chotim; Ratih Christiana; Andika Hady Pratama (Universitas PGRI Madiun, 2015)
Ex-psychotic individuals encounter many difficulties in the process of socializing andreturned to the environment, so that the necessary training skills before returning to thefamily and society. The purpose of this study was (1) To determine the effort to improvethe social and economic independence of individual ex-psychotic through vocationalskills training in the Social Rehabilitation Unit Ex Psychotic Social Service of East JavaProvince, (2) To determine the effectiveness of vocational skills training to improve socialand economic independence of the individual ex-psychotic The Social Rehabilitation UnitEx Psychotic Social Service of East Java Province.Writing method using a case studyapproach to field studies (field research) combined with literature (library research).This community service is a descriptive research, data analysis using qualitative analysiswith interactive model. The analyzed data is the data rate of socio-economicindependence of individuals before and after the psychotic ex vocational skillstraining.This research with two activities that make the carpet of material raffia rope andwooden crafts. Potential outcomes include training in order to improve their socioeconomicindependence, product copyrighted works, a national scientific journals andstrengthening the role of counselors and social services functions.